The National and International Studio Artists Program 1995-96 - Ribettes, Jean-Michel (New York : Institute for Contemporary Art, 1996)
Allen, Heather ; Cai Guo-Qiang ; Ceibal, Alfredo ; Chu, Ken ; Hand, Brian ; Jones, Mathew ; Lislegaard, Ann ; Lopez, Diana ; Meierhofer, Christine ; Moser, Claudio ; Park, Hwa Young ; red, p.t.t. ; Silitch, Jennifer ; van Warmerdam, Marijke
biografie
This catalogue introduces the fourteen participating artists of the 1995-96 program and is published on the occasion of an exhibition of their work at 80 Lafayette Street from May 3 through 31, 1996
Engels
boek